Recent Progress in 1D Contacts for 2D‐Material‐Based Devices. Issue 39 (29th August 2022) - Choi, Min Sup; Ali, Nasir; Ngo, Tien Dat; Choi, Hyungyu; Oh, Byungdu; Yang, Heejun; Yoo, Won Jong
Abstract: Recent studies have intensively examined 2D materials (2DMs) as promising materials for use in future quantum devices due to their atomic thinness. However, a major limitation occurs when 2DMs are in contact with metals: a van der Waals (vdW) gap is generated at the 2DM‐metal interfaces, which induces metal‐induced gap states that are responsible for an uncontrollable Schottky barrier (SB), Fermi‐level pinning (FLP), and high contact resistance ( R C ), thereby substantially lowering the electronic mobility of 2DM‐based devices. Here, vdW‐gap‐free 1D edge contact is reviewed for use in 2D devices with substantially suppressed carrier scattering of 2DMs with hexagonal boron nitride (hBN) encapsulation. The 1D contact further enables uniform carrier transport across multilayered 2DM channels, high‐density transistor integration independent of scaling, and the fabrication of double‐gate transistors suitable for demonstrating unique quantum phenomena of 2DMs. The existing 1D contact methods are reviewed first. As a promising technology toward the large‐scale production of 2D devices, seamless lateral contacts are reviewed in detail. The electronic, optoelectronic, and quantum devices developed via 1D contacts are subsequently discussed. Finally, the challenges regarding the reliability of 1D contacts are addressed, followed by an outlook of 1D contact methods. Abstract : Van der Waals gap‐free 1D contacts to 2D materials, toward their large‐scale application to 2D electronic and quantum devices, are reviewed. 1D edge contacts enable low contact resistivity, scattering‐free carrier transport, high‐density transistor integration, and double‐gate transistor operation. In addition, an outlook of the 1D contact methods is presented.